2018
DOI: 10.1042/bsr20171509
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in relation to the poor functional outcomes in nondiabetic patients with ischemic stroke

Abstract: To assess the hypothesis that vitamin D, reflected by 25-hydroxyvitamin D (25(OH) D) would be associated with higher risk of poor functional outcomes amongst nondiabetic stroke patients. The present study was conducted in Nanchang, China. Serum concentration of 25(OH) D and National Institutes of Health Stroke Scale (NIHSS) were measured at the time of admission. Functional outcome was measured by modified Rankin scale (mRS) at 1 year after admission. Multivariate analyses were performed using logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Previous studies had suggested that different variables recorded on admission were associated with poor outcome in stroke patients, for example insulin resistance [ 27 ], vitamin D deficiency or 25-hydroxyvitamin D [ 28 , 29 ], fatty acid-binding protein 4 [ 30 ], C-reactive protein, and homocysteine [ 31 ]. However, most of these biomarkers were modest predictors of outcome and unable to improve the prognostic accuracy of the NIHSS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had suggested that different variables recorded on admission were associated with poor outcome in stroke patients, for example insulin resistance [ 27 ], vitamin D deficiency or 25-hydroxyvitamin D [ 28 , 29 ], fatty acid-binding protein 4 [ 30 ], C-reactive protein, and homocysteine [ 31 ]. However, most of these biomarkers were modest predictors of outcome and unable to improve the prognostic accuracy of the NIHSS.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, vitamin D deficiency in stroke patients preceded stroke, and the prevalence of vitamin D deficiency is more evident in stroke patients than general medical patients. On the other hand, vitamin D supplementation in post-stroke patients may play a role in the prevention of recurrent stroke and improves the functional outcome after stroke [ 147 , 148 , 149 , 150 ].…”
Section: Vitamin D Deficiencies and Ischemic Strokementioning
confidence: 99%
“…In China, the annual stroke mortality rate is approximately 1.6 million, which has become the leading cause of deaths and adult disability [ 1 ]. The age-standardized incidence and mortality rates were 1114.8 per 100000 people, 246.8 and 114.8 per 100000 person-years, respectively [ 2 ].…”
Section: Introductionmentioning
confidence: 99%